Is labor export good development policy? - Ernesto M. Pernia (University of the Philippines, School of Economics (UPSE), 2008)
Labor migration began to be promoted in the late 60s or early 70s by a number of Asian countries burdened by problems of unemployment, poverty, and scant foreign exchange. However, labor export was generally intended to be a stop-gap measure while governments were trying to implement policy reform to whip their economies into shape. Indeed, labor migration as policy has largely faded in many of our Asian neighbors but remains a major development policy plank in our country. What has made the Philippines specially cut out to be a labor exporter? What are the benefits and costs of migration? Is the export of labor sustainable? Are we content with being a labor exporter? Is there a need to rethink the country's labor export policy?
Keywords: 330; Internationale Arbeitsmobilität; Asien